Correction of carotid-jugular traumatic fistula using a bovine pericardial patch - Sales,Werther Souza (2014)
Carotid-jugular fistulae are rare, but habitually cause morbidity and mortality. They are often linked with penetrating trauma, primarily caused by gunshots. This report describes the case of a patient who was the victim of a gunshot wound to the left cervical area, provoking a carotid-jugular arteriovenous fistula and occlusion of the common carotid artery. The fistula was corrected by ligature of the internal jugular vein and arteriorrhaphy of the left common carotid artery with a bovine pericardium patch.